Dynamics of Democracy in Public Policy: Challenges and Opportunities for the Indonesian Legal System - Intan Hanisa; I Gusti Ketut Ayu Rachmi Handayani; Lego karjoko (Yayasan Multidimensi Kreatif, 2024)
In the face of globalisation and complex socioeconomic concerns, democracy emerges as a critical factor in determining Indonesian public policy. This study dives into the dynamic interaction of democracy within the field of public policy, analysing its implications for Indonesia's legal environment. The major emphasis is on illuminating the difficulties that the legal system has in balancing multiple public opinions and goals during the governing process. This research takes a multidisciplinary approach, incorporating elements from legal political theory, legal sociology, and public policy theory, to reveal a nuanced understanding of democratic processes, institutional roles, and the intricate interplay between policy formulation and the legal framework. The findings highlight the considerable stresses that the dynamic character of democracy places on Indonesia's legal system. The difficult balance between protecting individual rights, fulfilling public interests, and maintaining societal stability is one of the challenges. These problems present possibilities to increase public engagement in policymaking, improve the operation of legal institutions, and design responsive legal enforcement mechanisms that are sensitive to the dynamic aspects of democracy. This research provides important insights into Indonesia's symbiotic link between democracy, public policy, and the legal system. The consequences guide targeted policy and legislative improvements that not only strengthen democratic foundations but also provide justice and legal security for every Indonesian person.